Harnessing new sources of economic strength to achieving sustainable development goals in Nigeria - Babatunde Wasiu Adeoye; Onyebuchi Iwegbu (The Nigerian Journal of Energy & Environmental Economics, 2020)
There were many failures recorded in the execution of the Millennium Development Goals which elapsed in 2015; a major cause of this was the limited resources in financing the programmes. The Sustainable Development Goals have been rolled out with higher number of goals as well as targets which elapses in 2030. The Nigerian economy is just recovering from recession and is currently faced with high debt profile coupled with oil price fluctuations. Thus, to finance the sustainable development goals, Nigeria must look away from the current production capacity by harnessing other opportunities that awaits her. This study therefore uses exploratory style of investigation to analyse the other sources of economic strength in achieving the sustainable development goals in Nigeria. From the exploratory investigation, the study found that expansion and massive development in Agribusiness through improvement in the agricultural value chain remains a viable new source of economic strength; this is because it has the ability to reduce massive importation of such product thereby reducing the demand gap. More also, there will be rapid export of such products thereby increasing foreign earnings which further creates massive employment opportunities for the people. Additionally, massive investment in tourism and investment in solid minerals are viable sources of economic strength in achieving the sustainable development goals.
Keywords: O21; O39; 330; Economic Strength; Sustainable Development Goals